FIVE-YEAR OBSERVATION OF THE PATIENT WITH SYSTEMIC TUBERCULOSIS AND HIV-INFECTION - TATYANA V. Pyanzova; NATALIA V. Luzinа; OLGA N. Kononchuk (Фундаментальная и клиническая медицина, 2018)
Here we describe the 5-year-follow-up of a female suffering from both tuberculosis (TB) and human immunodeficiency virus (HIV) infection. The management of the patient was particularly complicated due to systemic tuberculosis, multiple organ dysfunction syndrome, weakened immunity, and treatment intolerance. The patient received highly active antiretroviral therapy (HAART) for the whole period of follow-up, with two courses of anti-TB treatment over 39 months. Despite the development of an immune reconstitution inflammatory syndrome, aggressive treatment prevented the death and stabilized clinical course, with the further successful TB eradication. Five years after the diagnosis, we did not observe any signs of TB relapse. Patient’s general conditions was satisfactory. Immune status has been also improved, presumably due to HAART. We conclude that even patients with HIV infection combined with systemic TB may have a favorable prognosis.